Masculinity Ideology and Gender Equality: Considering Neosexism - Carmen Martínez (Anales de Psicología, 2013)
The aims of this study are to investigate the relationship among traditional masculinity ideology, neosexism, and gender equality. Specifi-cally we tested the effect of neosexism as a mediational variable. As ex-pected, our results showed that men maintain more traditional masculinity ideology and more neosexist beliefs than women. Also masculinity ideology is negatively related to gender equality in men, but in women there is no re-lationship. The results of the mediation tests confirm that masculinity ide-ology is a good predictor of gender equality and it is mediated by neosex-ism, but only for men. The relevance of these findings with reference to neosexism as an obstacle to equality is discussed.